VD_FINDINFO Jug / 2014 / 60 vom 11. September 2013 - VD Tribunal cantonal (2013)
LOI FÉDÉRALE SUR LES STUPÉFIANTS ET LES SUBSTANCES PSYCHOTROPES | 40 CP, 47 CP, 49 CP, 50 CP, 51 CP, 19 al. 1 LStup, 19 ch. 2 LStup, 19 LStup